METODE CHEAPEST INSERTION HEURISTIC PADA SISTEM INFORMASI GEOGRAFIS TEMPAT WISATA DI KABUPATEN DELI SERDANG BERBASIS ANDROID - Pohan, Syafaat Habib; Suendri, Suendri; Andriana, Septiana Dewi (JISTech (Journal of Islamic Science and Technology), 2023)
Geographic Information System (GIS) is a system created using information derived from processing a number of data, namely geographic data or data located on the earth's surface. Geographic Information Systems can be used in various fields, one of which is as a travel planning and tourist location. The lack of information conveyed on tourism in Deli Serdang Regency is one of the obstacles for people who want to travel. In this thesis, a Geographic Information System application for tourism in Deli Serdang Regency is developed which has detailed tourist information and the selection of the shortest travel route and alternative tours. To determine the shortest route and alternative travel, use the Cheapest Insertion Heuristic Algorithm. Then it is hoped that the community can be helped in planning tourist trips in Deli Serdang Regency. This application utilizes the google maps API as a virtual map provider which will later display tourist location points in Deli Serdang Regency. In addition, this application is also equipped with tourist list information along with tourist details that can be accessed by the public as a reference for traveling.